Efektifitas Permainan Tradisional Engklek terhadap Penguasaan Konsep Pembelajaran Tematik Peserta Didik Kelas III Madrasah Ibtidaiyah - Rofiatun Nisa’ (Fakultas Agama Islam Universitas Billfath, 2022)
The application of the traditional engklek game as a learning method by inviting students to play is one of the variations of learning that is favored by children and is able to train students in mastering the thematic learning concepts. This research is important to be researched in order to provide solutions to the low mastery of thematic learning concepts in Madrasah Ibtidaiyah which is still happening so that learning objectives can be implemented properly. The method in this study uses quantitative to test students after being given treatment in the form of applying the traditional engklek game. The research instrument used an observation and test form. The data analysis technique in this study is looking for validity, reliability, normality and linearity tests, and hypothesis testing with a t-test. The results obtained in the research conducted in class III in MI in Maduran District, Lamongan Regency, it can be concluded that 1) the level of interest in the engklek game 74% are included in the good category, meaning that the traditional engklek game can be said to be feasible as one of the suitable learning media to be applied to students of Madrasah Ibtidaiyah. 2) The level of mastery of students' concepts is 79% included in the high category, meaning that students' mastery of concepts in learning has been able to master thematic learning concepts in class III. 3) The effectiveness of the engklek game on students' concept mastery based on hypothesis testing is obtained tcount > ttable (4.163 > 2.101), meaning that the use of the engklek game is a new and varied method to be used in thematic learning.